Optimal Tax Administration - Keen, Michael (IMF Working Papers; Working Paper ;, 2017)
This paper sets out a framework for analyzing optimal interventions by a tax administration, one that parallels and can be closely integrated with established frameworks for thinking about optimal tax policy. Its key contribution is the development of a summary measure of the impact of administrative interventions-the 'enforcement elasticity of tax revenue'-that is a sufficient statistic for the behavioral response to such interventions, much as the elasticity of taxable income serves as a sufficient statistic for the response to tax rates. Amongst the applications are characterizations of the optimal balance between policy and administrative measures, and of the optimal compliance gap.